2017
DOI: 10.4314/jasem.v20i4.5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hookworm infections and some haematological parameters amongst primary and secondary schools children in Aba Metropolis, Abia State, Nigeria

Abstract: Hookworm infections and some haematological parameter among children were assessed in five different schools in Aba metropolis, Abia State, Nigeria. Blood and Stool samples were collected and analysed, following ethical approval and consent from parents and teachers of the subjects. Stool samples were analyzed using standard parasitological technique, from the blood samples, Haemoglobin (Hb) levels, Esinophils and white blood cell counts (WBC) were determined. Out of 1500 samples examined, 120 (8.0%) were posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…This suggested that this age group contribute more to the transmission of hookworm infection than other age groups. Dada-Adegbola et al (2005), Ezeaguna et al (2010) and Abah and Wokem (2016) supported this finding and reported the highest prevalence among children aged 12-17 years, than other age groups. These corroborate Crompton (2000) who suggested that teenagers and pregnant women were more at risk of hookworm and hookworm diseases such as iron deficiency anaemia than any other age group.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…This suggested that this age group contribute more to the transmission of hookworm infection than other age groups. Dada-Adegbola et al (2005), Ezeaguna et al (2010) and Abah and Wokem (2016) supported this finding and reported the highest prevalence among children aged 12-17 years, than other age groups. These corroborate Crompton (2000) who suggested that teenagers and pregnant women were more at risk of hookworm and hookworm diseases such as iron deficiency anaemia than any other age group.…”
Section: Discussionmentioning
confidence: 72%
“…of Abah and Wokem (2016) in Aba Metropolis, Abia State, Adeyeba and Tijani (2002), Odebunmi et al, (2007) and Kemajou et al (2017) in Igbo-ora in Oyo State, Vom, Plateau and Elele, Rivers-State Nigeria, respectively. The environment of these schools and the socio-cultural habits of the pupils could be responsible for the relatively high prevalence of hookworm infection in these areas.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations